The outcome of management of acute pancreatitis - Nagarjuna, T. R.; H. L., Prasad H. L. (International Journal of Research in Medical Sciences, 2017)
Background: Acute pancreatitis is a potentially life threatening disease. The initial management of patients with pancreatitis focuses on establishing the diagnosis, estimating its severity, addressing the major symptoms (i.e., pain, nausea, vomiting, and hypovolemia), and limiting its progression. Therefore, the present study has been undertaken to record the outcome of management of acute pancreatitis. Methods: The study population consisted of 40 cases of acute pancreatitis that fulfilled the diagnostic criteria. For assessing severity, Ransons and APACHE 2 systems were used. For Patients with <2 Ransons signs on admission pancreatitis immediate ERCP with ES followed by cholecystectomy. For Patients >2 Ransons signs on admission pancreatitis management was decided after 48 hrs of conservative management. Chi-square tests were employed to find out the difference between groups of frequencies obtained for the specific statements. A P value of less than 0.05 was considered statistically significant. Results: Out of 40 patients, Males were (55%) and (45%) were females. Majority of patients were belonging to the age group of 41-60 (42.5%) with a median age of 37 yrs in our study 14 patients had <2 Ransons signs. Out of which 9 underwent ERCP+ES+open cholecystectomy and 5 underwent ERCP+ES+lap cholecystectomy. Out of 8 cases of patients with more than 2 ransons signs conservative management was followed for 48 hours. 4 of them, upon subsidence of symptoms underwent open cholecystectomy. Conclusions: Predicting the prognosis of a patient with acute pancreatitis at admission forms a very important strategy in management of acute pancreatitis, which will enable to practice guidelines for standardization of management of the patient which will in turn translate into improved outcomes.